Interaction between Warfarin and the Herbal Product Shengmai-Yin: A Case Report of Intracerebral Hematoma - Su, Qun (Yonsei University College of Medicine, 2010)
A 71-year-old man was stable on warfarin (2.25 mg daily) therapy with an international normalized ratio (INR) of 1.8-2.2 after a heart valve replacement surgery. Recently, he consumed the liquid-like herbal product called shengmai-yin (10 mL daily) against medical advice. Seven days after the daily consumption of shengmai-yin, he was admitted to the intensive care unit because of consciousness disturbance [Glasgow Coma Scale (GCS) score 7] with an INR of 5.08. Head computed topography revealed intracerebral hematoma in the left temporoparietal region. Both warfarin therapy and the herbal product were withdrawn. At the same time, therapy with intravenous vitamin K(1) 40 mg was started. On the second day of admission, craniectomy was performed to remove the intacerebral hematoma under general anesthesia. He remained confused and restless for 2 days, but then showed progressive recovery in the consciousness level as well as motor and verbal functions. Shengmai-yin contains herbal ingredients that can interact with warfarin. The Drug Interaction Probability Scale (DIPS) indicated that warfarin and shengmai-yin were highly probable causes of intracerebral hematoma. Patients on warfarin therapy should be discouraged from taking herbal medicines, especially preparations that are already known to have antiplatelet and antithrombotic effects.